Metal-free, Tf2NH-catalyzed 1, 6-conjugate addition of imidazopyridine to para-quinone methides: easy access to C3-functionalized triarylmethane imidazopyridine - Khonde, Nilesh S.; Said, Madhukar S.; Sabane, Jagjivan K.; Gajbhiye, Jayant M.; Kumar, Pradeep (Tetrahedron, 2021)
An inexpensive and commercially available Tf2NH-catalyzed 1,6-conjugate addition of imidazopyridine (IMPY) heterocycles to para-quinone methides (p-QMs) is reported. The present transformation provides a diverse class of C3-functionalized triarylmethanes heterocyclic derivatives of imidazopyridine. These metal-free transformations provided a very broad substrate scope of conjugate addition product with a high yield up to 97% within a short duration. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: 1; 6-Conjugate addition; Bronsted acid; C3-functionalization; Imidazopyridine; para-Quinone methide

Novel 3-fluoro-4-morpholinoaniline derivatives: synthesis and assessment of anti-cancer activity in breast cancer cells - More, Namita A.; Jadhao, Nitin L.; Meshram, Rohan J.; Tambe, Prajakta; Salve, Rajesh A.; Sabane, Jagjivan K.; Sawant, Sanskruti N.; Gajbhiye, Virendra; Gajbhiye, Jayant M. (Journal of Molecular Structure, 2022)
Heterocyclic morpholine compounds are well-known for their anti-cancer activity. In this study, novel morpholine and its sulfonamide derivatives were designed and synthesized as potential anti-tumor agents. The new compounds were obtained from amine derivatives via nucleophilic addition reactions, providing the desired products in 70 to 90% yield. The docking analysis was performed for all thirty-one compounds. Out of them, we represent the docking poses for compounds NAM-5 and NAM-7 as representatives. After docking analysis, compounds NAM-5 and NAM- 7 were tested for in vitro antitumor activity against breast cancer cell lines (MCF-7 and MDA-MB-231) and healthy mouse embryonic fibroblast cell line (3T3L-1). Amongst these, sulfonamide group-containing compound NAM-5 showed significant anti-proliferative activity with IC50 of 1.811 mu M and 2.143 mu M for MCF-7 and MDA-MB-231 cells, respectively. On the other hand, NAM-7 showed good anti-proliferative activity against MCF-7 (IC50 1.883 mu M) but slightly lower activity against MDA-MB-231 cells (IC50 4.688 mu M). The activity of both the compound was also tested on 3T3L-1 Cell line which showed activity similar to clinically approved anti-cancer drug doxorubicin (DOX). The cell death analysis by flow-cytometry confirmed apoptosis mediated cell death in 3T3L-1, MCF-7 and MDA-MB-231 cells when treated with the NAM-5 and NAM-7, respectively. The results demonstrated that the synthesized sulfonamide derivatives have significant potential as anti-cancer agents and have a substantial importance in cancer therapeutics with favourable safety profile. Structural analysis of docked poses of sulfonamide derivatives attempts to shed light on the structural basis of sulfonamide derivatives based anti-cancer effect. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Anticancer activity; Apoptosis; Breast cancer; Heterocyclic compounds; Morpholine; Sulfonamide

4-aminoantipyrine linked bis-1,2,3-triazole based probes for Cu(II) sensing - Lal, Bajrang; Kumar, Sachin; Tittal, Ram Kumar; Singh, Gurleen; Singh, Jandeep; Ghule, Vikas D.; Mathpati, Ramling S.; Sabane, Jagjivan K. (Journal of Molecular Structure, 2024)
Herein, two molecular probes of 4-aminoantipyrine-linked bis-1,2,3-triazoles have been studied for metal ion sensing applications. The crystal structure of one of the probes named as 4,4 `-((4,4 `-(((1,5-dimethyl- 3- oxo- 2- phenyl- 2,3- dihydro- 1H- pyrazol- 4-yl) azanediyl) bis(methylene))bis(1H-1,2,3-triazole-4,1-diyl))bis(methylene))dibenzonit rile (3b) crystalizes in Monoclinic crystal system in P 1 21/n 1 space group. Both probes responded more strongly and selectively to Cu(II) than other tested metal ions (K+, Na+, Mg2+, Ba2+, Ca2+, Cr3+, Mn2+, Co2+, Zn2+, Cd2+, Ni2+, Hg2+, and Pb2+). Job's plot suggested a 1:1 stoichiometric ratio of ligand and metal ion. Both probes showed an association constant of 2.48 x 10(3) M-1 and 3.73 x 10(3) M-1 through Benesi-Hildebrand (B-H) plot. The geometries of both probes and their complexes were optimized by DFT using B3LYP/6-311 G(d,p) and B3LYP/LanL2DZ basis sets, and properties were supported by Mulliken atomic charge and Molecular electrostatic potential. Molecular docking on both probes and their complexes with Type-II topoisomerases(PDB ID: 4G0V) protein was conducted to foretastes anticancer activity.
Keywords: 2; 3-Triazole; 4-aminoantipyrine; and Molecular docking; Bis-1; Cu2+ Sensor; DFT; X-ray crystallography

H5IO6, as an efficient reagent for the aromatization of tetrahydro-β-carbolines: total synthesis of norharman, harmane, harmine, kumujian-C, and orthoscuticellines B - Sabane, Jagjivan K.; Gaikwad, Sunil V.; Gajbhiye, Jayant M.; Kumar, Pradeep (ChemistrySelect, 2026)
A new method is reported for the synthesis of beta-carbolines and their derivatives using H5IO6 in DMSO solvent. The method is mild and efficient for oxidative decarboxylation and aromatization of tetrahydro beta-carbolines (TH beta C), resulting in good to excellent yields (70% to 88%) of beta-carbolines. This protocol has further been utilized for the synthesis of beta-carbolines based natural products, for examples, norharmane, harmane, harmine, Kumujian-C, and Orthoscuticellines A and B.
Keywords: aromatization; beta-carboline; H5IO6; Harmine; orthoscuticellines; Oxidative